Optimizing Financial Risk Prediction for Loan Approval Decisions - Khalifatur Rauf; Adi Cahyo Kuswijayanto; Ella Kristiantini Susan (UIN Sunan Kalijaga Yogyakarta, 2026)
Accurate financial risk prediction is essential for effective loan approval decision-making, particularly in data-driven financial systems. This study investigates the influence of feature selection strategies on the performance of machine learning models for loan approval prediction using the publicly available Kaggle